2022
DOI: 10.1039/d2fo00552b
|View full text |Cite
|
Sign up to set email alerts
|

Urolithins: potential biomarkers of gut dysbiosis and disease stage in Parkinson's patients

Abstract: A gradual increase in urolithin non-producers (UM-0) concomitant with a decrease in urolithin producers (UM-A and UM-B) was observed as the disease severity increased in Parkinson's disease patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Data processing, chimeric sequence removal, sequence alignment, and 16S rRNA gene sequence clustering were performed as described elsewhere to obtain the taxonomic classification. 8,27 Gordonibacter DNA amplification was achieved in an ABI 7500 qPCR system as previously described. 19,28 The Enterocloster and Ellagibacter-specific primers and probes designed in the present study were used following the qPCR protocol described above.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Data processing, chimeric sequence removal, sequence alignment, and 16S rRNA gene sequence clustering were performed as described elsewhere to obtain the taxonomic classification. 8,27 Gordonibacter DNA amplification was achieved in an ABI 7500 qPCR system as previously described. 19,28 The Enterocloster and Ellagibacter-specific primers and probes designed in the present study were used following the qPCR protocol described above.…”
Section: Food and Function Papermentioning
confidence: 99%
“…During PD development, microbiota changes can be accompanied by reduced concentrations of branched-chain amino acids (BCAAs) and aromatic amino-acids in comparison with the healthy control group [ 128 ]. It has been demonstrated that the alteration of the metabolites occurred, especially during disease progression [ 129 ]. Experimental results indicate the correlation between PD and mitochondrial dysfunction.…”
Section: Microbiota Metabolites and The Severity Of Neurodegenerative...mentioning
confidence: 99%
“…GM and host metabolism are strictly interconnected [ 94 , 95 ]. Indeed, because of dysbiosis, lipid, amino acid and energy metabolism are often dysregulated in PD patients [ 96 , 97 , 98 , 99 , 100 ]. Studies show that a decrease in branched chain and aromatic amino acid biosynthesis, carbohydrate fermentation and butyrate synthesis is accompanied by an upregulation in lipopolysaccharides (LPS) production, bacterial type III secretion system biosynthesis (a complex bacterial structure involved in virulence) and proteolytic fermentation, which trigger inflammation and promote the release of harmful metabolites (i.e., phenylacetylglutamine and p-cresol) [ 50 , 101 , 102 ].…”
Section: Parkinson’s Disease and Gut Microbiota: Links And Mechanismsmentioning
confidence: 99%
“…For example, dementia development may be predicted by low levels of plasma TMAO measured at an early stage of the disease, thus serving as prognostic marker [ 164 ]. Moreover, disease severity has been associated with lower urine levels of urolithin, an anti-inflammatory molecule produced by the gut microbiota upon polyphenols intake [ 100 ]. When low, urolithin reflects a condition of dysbiosis characterized by an overgrowth of the pro-inflammatory Enterobacteriaceae at the expense of the beneficial Lachnospiraceae and Gordonibacter [ 100 ].…”
Section: Parkinson’s Disease and Gut Microbiota: Biomarkers And Drug ...mentioning
confidence: 99%
See 1 more Smart Citation